The Use of Personal Knowledge Management Initiatives by Teachers in Poland. Contribution to the Discussion - Figurska, Irena; Piekarski, Grzegorz; Piotrów, Ewa (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article discusses the issues related to personal knowledge management (PKM) and initiatives undertaken in this area by a professional group of teachers. These issues are still insufficiently researched, and thus cognitively interesting and requiring further exploration. The aim of the study was to determine the level of teachers' initiative in the area of personal knowledge management, with reference to the relationships between the variables characterizing the surveyed teachers, such as: gender, age, seniority, type of educational institution and the position held. In the study, conducted by means of a diagnostic survey method among 169 professionally active teachers, the author's Questionnaire of Personal Knowledge Management Initiatives was used. The obtained research results were statistically analyzed using the PSPP program, Gnu General Public License Version 3. The data were processed using the ANOVA analysis of variance. The applied method of standard deviations showed that the largest group of the surveyed teachers presents an average level of initiative in the field of personal knowledge management. Based on the obtained results, it can also be concluded that: women, teachers with the longest seniority, from the oldest age group, holding managerial positions; employed in kindergartens and educational non-school institutions, are characterized by a higher level of initiative in the field of personal knowledge management. The obtained research results are of practical importance both for teachers and for the organizations in which they work. They may also contribute to the introduction of new solutions in the education of future teachers at the university level, as well as to the organization of training and workshops improving and developing personal knowledge management skills among professionally active teachers.